Influence of the network structure and void content on hygrothermal stability of resol resin modified with epoxy-amine - Manfredi, Liliana Beatriz (2006)
Epoxy-amine was blended with two resol resins to study the influence of the fined network and void content on the water absorption of these systems. To characterize the network structure of the blends, infrared analyses were performed. It was observed that a diminution in the crosslink density of the network and the reaction between the epoxy and resol have been occurred. From dynamic-mechanical analyses, a diminution in the Tg value and an increment in the height of the tan δ peak with the epoxy-amine content added to the resol were observed. Thermogravimetric analysis showed that the thermal stability of the resol was reduced by the addition of epoxy-amine as well as a lesser crosslink network for the blends with higher epoxy-amine content. The maximum water uptake and the diffusion coefficient were related with the chemical structure and void content of the specimens. On one hand, the maximum water uptake was observed to depend on the void content of the blends. On the other hand, the diffusion coefficient appears to be related with the local motions of the polymeric chains and with the hydrophilic character of the materials. This behavior was observed for the two resols studied. © 2006 Wiley Periodicals, Inc.